Mechanism of Mass Spectral Fragmentation of Mixed-Ligand Cobalt(III) Complexes with Heterocyclic Dithiocarbamates and Tetraazamacrocyclic Ligand - Babic-Samardzija, Ksenija; P. Sovilj, Sofija (Asian Journal of Chemistry, 2010)
The mass spectral fragmentation of three mixed-ligand Co(III) complexes of the general formula [Co(Rdtc)cyclam](ClO4)2 (1)- (3), where cyclam and Rdtc refer to 1,4,8,11-tetraazacyclotetradecane and 2-methylpiperidine-(2-Mepipdtc), 3-methylpiperidine( 3-Mepipdtc) and 4-methylpiperidine-(4-Mepipdtc) dithiocarbamates, respectively, have been investigated. It is shown to be of mechanistic significance, clarifying the major products of their fragmentation. A possible mechanism entails a multi-step decomposition process, which can also be well separated into individual steps. Every step is determined to know the nature ofthe intermediates.